Knowledge Mapping of Digital Ethics in Education: A Bibliometric and Science Mapping Analysis - Farid Fauzi (International Journal of Humanities, Education, and Social Sciences, 2026)
Although digital ethics has become increasingly important in education, systematic evidence on its global research structure and thematic development remains limited. This study aims to map global research on digital ethics in education from 2015 to 2025 using bibliometric analysis and science mapping techniques. Data were retrieved from Scopus, yielding 782 documents published in 466 sources and involving 3,993 authors. The analysis was conducted using Bibliometrix and VOSviewer to examine publication trends, citation impact, collaboration networks, keyword co-occurrence, co-citation patterns, thematic mapping, and thematic evolution. The findings reveal rapid growth in publication output and interdisciplinary collaboration, indicating the expanding scholarly relevance of digital ethics in educational research. Core keywords, including ethics, education, higher education, and female, form the intellectual backbone of the field. Network, overlay, and density visualizations show a thematic shift from methodological and COVID-19-related topics toward emerging issues such as digital literacy, AI literacy, generative AI, academic integrity, equity, and curricula. High research density remains concentrated around ethics and education, whereas AI-related themes are still comparatively underexplored. These findings highlight opportunities for future research on ethical AI literacy, AI governance, and responsible AI integration in educational curricula. This study contributes a comprehensive knowledge map by identifying leading actors, thematic domains, and research gaps, offering practical guidance for scholars, policymakers, and practitioners seeking to promote ethical, equitable, and accountable digital transformation in education.